Problematika Membaca Teks Bahasa Arab Pada Mahasiswa Pendidikan Bahasa Arab UIN Syarif Hidayatullah Jakarta - Sessas, Bunga; Ambarwati , Zakiyyah; Perkasa, Iham; Umbar, Kisno (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2023)
Learning Maharah Qiroah at UIN Syarif Hidayatullah Jakarta is an important subject during semesters 1-3. This course significantly helps students in reading Arabic texts. However, achieving success in this course requires students to overcome various problems they face, both linguistic and non-linguistic. This study follows a descriptive approach and collects data through observation and interviews. The results of this study highlight the problems faced by Arabic Language Education Students in reading Arabic texts at Syarif Hidayatullah State Islamic University Jakarta, and provide possible solutions. Firstly, many students face linguistic and non-linguistic difficulties while learning Maharah Qiroah. Secondly, self-motivation is crucial for students to overcome these difficulties. Additionally, providing interesting texts as a learning medium can encourage students to read more.